Investigating Factors Affecting the Adoption of Virtual Fitting Room in Iranian Sportswear Stores: Application of CAT Theory - Seyyed iman Ghaffarisadr; Farzad Nobakht Sareban (Research in Sport Management and Marketing)
Purpose: Trying on clothes in sportswear stores is a very time-consuming and tiring task. Virtual fitting rooms provides conditions where online consumers can try on the clothes they want before shopping. This technology has recently received much attention due to its commercial potential. However, this technology has not arrived to Iran yet, and it is obscure if the Iranian consumers accept it. In this research, the researcher is trying to investigate the factors affecting the acceptance of this technology by online sports consumers.Methods: This is an applied research. The mixed method was used, in which the Delphi technique was employed between experts of sportswear industry in the qualitative phase. In the quantitative phase, online consumers of sports products were selected as a sample. The snowball method was used to collect the subjects. Finally, 420 questionnaires were collected. The validity of the instrument was confirmed through the opinions of university professors and convergent validity. Cronbach's alpha and composite reliability were used to check the reliability. SPSS26 and Amos24 software were used for data analysis. Structural equation modeling was used to test the hypotheses and evaluate the overall fit. Results: The results showed the positive effect of all the factors including perceived usefulness, perceived ease of use, pleasure, arousal and dominance on the adoption of virtual fitting room by online sport consumers. Conclusion: The results of this research have practical implications for sports managers and retailers in relation to adopting the best management and marketing strategies to use virtual fitting rooms.